Pre-pubertal oocytes harbor altered histone modifications and chromatin configuration - Wasserzug Pash, Pe’era; Karavani, Gilad; Reich, Eli; Zecharyahu, Lital; Kay, Zehava; Bauman, Dvora; Mordechai-Daniel, Talya; Imbar, Tal; Klutstein, Michael (Frontiers in Cell and Developmental Biology, 2023)
Pre-pubertal oocytes are still dormant. They are arrested in a GV state and do not undergo meiotic divisions naturally. A multitude of molecular pathways are changed and triggered upon initiation of puberty. It is not yet clear which epigenetic events occur in oocytes upon pubertal transition, and how significant these epigenetic events may be. We evaluated epigenetic marker levels in mouse pre-pubertal and post-pubertal female oocytes. In addition, we evaluated H3K9me2 levels in human oocytes collected from fertility preservation patients, comparing the levels between pre-pubertal patients and post-pubertal patients. The chromatin structure shows a lower number of chromocenters in mouse post-pubertal oocytes in comparison to pre-pubertal oocytes. All heterochromatin marker levels checked (H3K9me2, H3K27me3, H4K20me1) significantly rise across the pubertal transition. Euchromatin markers vary in their behavior. While H3K4me3 levels rise with the pubertal transition, H3K27Ac levels decrease with the pubertal transition. Treatment with SRT1720 (histone deacetylase [HDAC] activator) or overexpression of heterochromatin factors does not lead to increased heterochromatin in pre-pubertal oocytes. However, treatment of pre-pubertal oocytes with follicle-stimulating hormone (FSH) for 24h - changes their chromatin structure to a post-pubertal configuration, lowers the number of chromocenters and elevates their histone methylation levels, showing that hormones play a key role in chromatin regulation of pubertal transition. Our work shows that pubertal transition leads to reorganization of oocyte chromatin and elevation of histone methylation levels, thus advancing oocyte developmental phenotype. These results provide the basis for finding conditions for in-vitro maturation of pre-pubertal oocytes, mainly needed to artificially mature oocytes of young cancer survivors for fertility preservation purposes.